اسلام کی معاشرتی تعلیمات کا دیگر آسمانی مذاہب سے تقابلی جائزہ: A comparative analysis of the social teaching of Islam with other heavenly relgion - Khadija Bibi; Mazhar Hussain Bhadroo (AL-IDRAK JOURNAL, 2023)
Islamic social teachings, like those of other religions, emphasize the importance of treating others with kindness, generosity, and respect. These teachings often include principles such as helping the needy, promoting economic fairness, and striving for peaceful coexistence. In Islam, concepts like "Zakat" (charitable giving) and "Sadaqah" (voluntary charity) encourage Muslims to support those in need and contribute to the well-being of society. The Quran and Hadith also stress the value of honesty, integrity, and compassion in interactions with others. Similarly, other religions have their own teachings that align with these values. For instance, Christianity emphasizes the importance of loving one's neighbor, caring for the marginalized, and seeking justice for all. Buddhism promotes concepts of empathy, non-violence, and detachment from material desires, which can contribute to social harmony. While each religion has its unique teachings, the common thread is the call to create a just, compassionate, and harmonious society, where individuals strive to uplift each other and contribute positively to the world around them. Islam, like other religions, has its unique teachings that differentiate it from other faiths. Some key differences include its beliefs about monotheism (the belief in one God), the role of Muhammad as the final prophet, the importance of the Quran as the holy book, the practice of praying five times a day, fasting during the month of Ramadan, and the concept of zakat (charitable giving). While there are similarities in ethical teachings among various religions, these distinct aspects set Islam apart from others like Christianity and Judaism. Remember, though, that religions are complex and diverse, and there can be variations in beliefs and practices within each one. Islamic social teachings share common themes with other religions in terms of promoting compassion, justice, and ethical behavior. Concepts like caring for the less fortunate, respecting human dignity, and fostering harmony among people are shared across various faiths, including Islam. While there are differences in practices and beliefs, the overarching goal of creating a just and equitable society is a common thread that runs through many religious teachings.